The Students' Religion Attitude: A Pattern of Pesantren Ramadhan for Senior High School Students - Hilma Pami Putri (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2020)
This study found that the activities of Pesantren Ramadhan which had been carried out for about 12 times gave positive meaning for high school students in Padang city. One of them is increasing of students' religious attitudes from daily worship like continuous dhuha prayer, fasting every Monday and Thursday, motivation to memorize the Koran and various other religious activities. The theory of someone’s religious diversity is influenced by knowledge, beliefs, implementation of worship, and appreciation of the religion they embrace. The higher a person's knowledge of religion, the higher the level of religious diversity they have. The method used in this research is descriptive-qualitative, which describes the behavior of students after attending the Pesantren Ramadhan then analyzed the material of the Islamic boarding school to be realized in daily life.